Oxygen sensors made by monolayer graphene under room temperature - Chen, C. W.; Hung, S. C.; Yang, M. D.; Yeh, C. W.; Wu, C. H.; Chi, G. C.; Ren, F.; Pearton, S. J. (My University, 2011)
The electrical resistivity of monolayer graphene exhibit significant changes upon expose to different concentration of oxygen (O(2)) at room temperature. The monolayer graphene, grown by chemical vapor deposition with perfect uniformity within 1 cm x 1 cm will attach O(2) molecules and enhance the hole conductivity, which will lead to a change of resistivity of graphene thin film. We quantified the change of resistivity of graphene versus different O(2) concentration and the detection limit of the simple O(2) sensor was 1.25% in volume ratio. (C) 2011 American Institute of Physics. [doi: 10.1063/1.3668105]